South Africa : Technical Assistance Report-Fiscal Regimes for Mining and Petroleum: Opportunities and Challenges. (IMF Staff Country Reports; Country Report, 2015)
This Technical Assistance report reviews South Africa's tax system and also examines the fiscal regime with a view to generating a sustainable revenue contribution from mining and petroleum in future. Mining has historically been the mainstay of the South African economy. Mineral exports remain the principal contributor to foreign exchange earnings on the current account. South Africa is not yet a significant producer of crude oil or natural gas. Oil and gas exploration nevertheless shows promise. Taxation is far from top of the list in current challenges facing the development of extractive industries in South Africa. The national goal of economic and social transformation in favor of Historically Disadvantaged South Africans has major impact on the mining sector.